Escola: as minas e os manos têm a palavra - Jovino, Ione da Silva (Universidade Federal de São Carlos, 2005)
The research has for main objective the relationship estabilisered between the black hip-hopper students and formal education. It seeks, from a Foucault style reference, the construction of the language, visions, feelings and significations that the young hip-hoppers associate with school. Describing itself as a study that attempts to stand between formal education and the hip-hop culture, this dissertation may contribute to the debate of hip-hop as a power, as a escape route for the black and poor youngsters. It also shows how hip-hop, as a culture apart has commenced such a skirmish for cultural positions within the school and has dislocated power arrangements.
Keywords: Educação - negros; Jovens; Escolas; Biopotência; Movimento hip hop; Black youger; School; Biopower; Hip-hop movement; CIENCIAS HUMANAS::EDUCACAO